The Effect of Transformational Leadership on the Performance of State Primary School Teachers in Ogan Komering Ulu - Qotrunnada, Emilda; Mellita, Dina (International Journal of Finance Research, 2025)
Teacher performance is one of the keys to successful implementation of learning in schools. To improve the quality of education through teacher performance, principals need to be forward-thinking leaders who guide and inspire teachers to be able and eager to work efficiently. Of the many factors that can affect teacher performance is leadership. Transformational leadership is a process by which leaders and subordinates strive to achieve a high level of morality and motivation. The purpose of this study was to analyze the influence of transformational leadership on the performance of public secondary school teachers in the middle school system. The research method used is the Partial Least Square (PLS) method using SmartPLS software version 4. The study sampled 100 teachers with positions as vice principals and class teachers using questionnaires. The data used in this study are primary data. After carrying out the study, it can be concluded that transformational leadership has no influence on teacher performance